Transposable elements are the primary source of novelty in primate gene regulation - Trizzino, Marco; Park, YoSon; Holsbach-Beltrame, Marcia; Aracena, Katherine; Mika, Katelyn; Caliskan, Minal; Perry, George H.; Lynch, Vincent J.; Brown, Christopher D. (Genome Research, 2017)
Gene regulation shapes the evolution of phenotypic diversity. We investigated the evolution of liver promoters and enhancers in six primate species using ChIP-seq (H3K27ac and H3K4me1) to profile cis-regulatory elements (CREs) and using RNA-seq to characterize gene expression in the same individuals. To quantify regulatory divergence, we compared CRE activity across species by testing differential ChIP-seq read depths directly measured for orthologous sequences. We show that the primate regulatory landscape is largely conserved across the lineage, with 63% of the tested human liver CREs showing similar activity across species. Conserved CRE function is associated with sequence conservation, proximity to coding genes, cell-type specificity, and transcription factor binding. Newly evolved CREs are enriched in immune response and neurodevelopmental functions. We further demonstrate that conserved CREs bind master regulators, suggesting that while CREs contribute to species adaptation to the environment, core functions remain intact. Newly evolved CREs are enriched in young transposable elements (TEs), including Long-Terminal-Repeats (LTRs) and SINE-VNTR-Alus (SVAs), that significantly affect gene expression. Conversely, only 16% of conserved CREs overlap TEs. We tested the cis-regulatory activity of 69 TE subfamilies by luciferase reporter assays, spanning all major TE classes, and showed that 95.6% of tested TEs can function as either transcriptional activators or repressors. In conclusion, we demonstrated the critical role of TEs in primate gene regulation and illustrated potential mechanisms underlying evolutionary divergence among the primate species through the noncoding genome.